2012
DOI: 10.1111/j.1745-3933.2012.01231.x
|View full text |Cite
|
Sign up to set email alerts
|

NGC 3801 caught in the act: a post-merger star-forming early-type galaxy with AGN—jet feedback

Abstract: In the current models of galaxy formation and evolution, AGN feedback is crucial to reproduce galaxy luminosity function, colour–magnitude relation and M•–σ relation. However, whether AGN feedback can indeed expel and heat up significant amount of cool molecular gas and consequently quench star formation is yet to be demonstrated observationally. Only in four cases so far (Cen A, NGC 3801, NGC 6764 and Mrk 6), X‐ray observations have found evidences of jet‐driven shocks heating the ISM. We chose the least expl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…An HST B-band (F435W) image is presented in Figure 1. 13 These images reveal filamentary structures in the central dust emission of NGC 1266, similar to those seen in other systems with outflows (e.g., NGC 3801; Das et al 2005;Hota et al 2012). A detailed analysis of the full set of HST data from this program will be presented in a future paper.…”
Section: The Hubble Space Telescopementioning
confidence: 62%
See 1 more Smart Citation
“…An HST B-band (F435W) image is presented in Figure 1. 13 These images reveal filamentary structures in the central dust emission of NGC 1266, similar to those seen in other systems with outflows (e.g., NGC 3801; Das et al 2005;Hota et al 2012). A detailed analysis of the full set of HST data from this program will be presented in a future paper.…”
Section: The Hubble Space Telescopementioning
confidence: 62%
“…2012; Greene et al 2012;Maiolino et al 2012). It has been suggested that the less powerful AGNs that populate the nearby universe may also be capable of driving molecular outflows and shutting down late-time SF in some local galaxies (Schawinski et al 2009;Chung et al 2011), and the number of such candidates has been increasing (Das et al 2005;Matsushita et al 2007;Alatalo et al 2011;Dasyra & Combes 2012;Hota et al 2012;Aalto et al 2012b;Morganti et al 2013;Sakamoto et al 2013). Of these intriguing local candidates for AGN-driven SF quenching, NGC 1266 (Alatalo et al 2011(Alatalo et al , 2013Davis et al 2012) provides a rare example of a host galaxy that is both non-starbursting and shows no evidence of a recent major merger or interaction (although see Aalto et al 2012b andSakamoto et al 2013…”
Section: Introductionmentioning
confidence: 99%
“…Its spectrum is extremely red, with weak emission lines. We cannot exclude that the AGN is in its last phase before reaching a quiescent state (Hota et al 2012). The source has symmetric jets, and it appears to be forming a disk.…”
Section: Appendix A: Notes On Individual Objectsmentioning
confidence: 94%
“…We have classified it as a probable XRG (or an intermediate between the X-and Z-shaped radio galaxies) based on its FIRST image shown in the top right panel of Figure 7. As it is known to be a post-merger star-forming galaxy (Hota et al 2012), its wings could even have formed owing to pre-merger gravitational interaction between the two galaxies. Coming to some other "probable" XRG candidates in the FR I domain (Figure 6), we find that a few of them (e.g., J1044+3540; see the bottom right panel of Figure 7) appear remarkably similar in radio morphology to the early lowresolution radio map of XRG NGC 326 (Fanti et al 1977), which is a classical example of an FR I XRG, on account of its prominent Figure 6.…”
Section: The Fanaroff-riley Classification For X-shaped Radio Galaxiesmentioning
confidence: 99%